2021
DOI: 10.37012/jkmp.v1i1.1186
|View full text |Cite
|
Sign up to set email alerts
|

Faktor yang Mempengaruhi Kejadian Anemia pada Ibu Hamil di Wilayah Kerja Puskesmas Lembursitu Kota Sukabumi (Analisis Data Sekunder)

Abstract: Anemia pada kehamilan merupakan salah satu masalah nasional karena mencerminkan nilai kesejahteraan sosial ekonomi masyarakat dan pengaruhnya sangat besar terhadap kualitas sumber daya manusia. Anemia pada ibu hamil disebut potensial membahayakan ibu dan anak. Tujuan dari penelitian ini adalah untuk mengetahui faktor yang mempengaruhi kejadian anemia pada ibu hamil di wilayah kerja Puskesmas Lembursitu Kota Sukabumi tahun 2020. Penelitian ini bersifat observasional dengan pendekatan cross sectional, jumlah sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 1 publication
2
1
0
4
Order By: Relevance
“…Pregnant women who work can experience stress caused by various factors originating from individual characteristics during pregnancy and related to the work they do (Sambara et al, 2010). The results of this study are in line with research conducted by Imaroh, Nugraheni, and Dharminto (2017), who found that there was a relationship between maternal employment status and hypertension in pregnant women where pregnant women with working status had a higher risk of 7.6 times suffering from gestational hypertension than pregnant women which do not work (Nugraheny & Prabandani, 2015). According to the researcher's assumptions, the predominance of hypertension in pregnancy in mothers who do not work can occur because, apart from work status factors, mothers also have other factors as triggers for hypertension in pregnancy, such as anxiety or problems experienced.…”
Section: Discussionsupporting
confidence: 90%
“…Pregnant women who work can experience stress caused by various factors originating from individual characteristics during pregnancy and related to the work they do (Sambara et al, 2010). The results of this study are in line with research conducted by Imaroh, Nugraheni, and Dharminto (2017), who found that there was a relationship between maternal employment status and hypertension in pregnant women where pregnant women with working status had a higher risk of 7.6 times suffering from gestational hypertension than pregnant women which do not work (Nugraheny & Prabandani, 2015). According to the researcher's assumptions, the predominance of hypertension in pregnancy in mothers who do not work can occur because, apart from work status factors, mothers also have other factors as triggers for hypertension in pregnancy, such as anxiety or problems experienced.…”
Section: Discussionsupporting
confidence: 90%
“…The results of the study found that there were as many as 17 respondents with an age that was not at risk but had hypertension in pregnancy. This is in line with the research of Imaroh et al (2018) which states that there is a relationship between age and the incidence of HDK. Maternal age is one of the risk factors for hypertension.…”
Section: The Relationship Between the Age Of Pregnant Women And The I...supporting
confidence: 91%
“…In the study of Imaroh et al (2018) it was found that the age of mothers <20 years and >35 years was 4.9 times greater in influencing risk factors for hypertension (Imaroh et al, 2018).…”
Section: The Relationship Between the Age Of Pregnant Women And The I...mentioning
confidence: 97%
“…Hal ini sejalan dengan penelitian Makmur & Fitriahadi (2020) yang menunjukkan terdapat hubungan signifikan antara umur dan kejadian hipertensi (15). Hasil penelitian ini juga sejalan dengan penelitian (Imaroh & Dharminto, 2018) yang menunjukan ada hubungan antara umur ibu dengan kejadian hipertensi, bahkan umur ibu merupakan salah satu faktor resiko terjadinya hipertensi (16). Ibu hamil yang berusia < 20 tahun mudah mengalami kenaikan tekanan darah dan lebih cepat menimbulkan kejang, sedangkan umur > 35 tahun juga merupakan faktor prediposisi untuk terjadinya preeklampisa, karena bertambahnya usia (17).…”
Section: Hubungan Usia Dengan Kejadian Hipertensi Pada Ibu Hamil DI R...unclassified